Introduction to the bayesian methodology of contemporary cosmology - Kurek, Aleksandra; Kukier, Łukasz; Szydłowski, Marek; Tambor, Paweł (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2009)
The Bayesian framework is used in reconstruction of modern cosmology which actually concentrates on estimation of model parameters. The authors demonstrate that observational cosmology should be treated as an effective theory of the Universe. It realizes dream of science proposed by logical empirism in some sense, i.e. science should be founded on empirical data from the very beginning, and it formulates and amplifies the hypothesis through new empirical data. They have also shown some limitations of the Bayesian approach as well as its advantages when this approach is applied to cosmology.